Word classes in modern English and their usage in English grammar - Habibulloyeva Gulchehra; Khushbakova Nasiba (Global Scientific Publishing, 2022)
This article defines the parts of speech in English language and gives definition of word classes in modern English. Besides, we tried to explain three criteria for determining the word class of a word and appropriate example are given for them
Keywords: verbs; nouns; adjectives; adverbs